Investigation of New Facility Location Fır Elvan Gıda - Dinçer, Tutku; Tuncer, Müge; Özgür, Müge; İnce, Buse; Bayramoğlu, Feyzanur; Altınyar, Aydan; YÜKSEKTEPE, FADİME ÜNEY (My University, 2019)
Elvan Gıda, established in 1952 as a small candy shop in Istanbul, started to manufacture sweet and chocolate to meet high quality confectionery demand with affordable prices. Elvan has 7 different production facilities located in Istanbul (5), Sakarya and Eskişehir. Currently, company is dealing with a problem of gathering all facilities in a single facility to eliminate fixed operating costs of each while covering desired increased capacity. In this study, an analytical approach will be proposed to solve the facility location problem of the company. First of all, the necessary data about distribution channels of finished goods, transportability, capacity of current and planned facilities, desired optimal distance to Ambarlı harbor and planned budget will be collected. According to determined criteria’s, AHP methodology will be used for selecting 5 promising potential alternatives by considering the executive boards’ evaluations. As a next step, a mathematical model will be developed to decide the least cost location alternative by considering both inbound and outbound transportation costs. Consequently, the optimal facility location with an aggregate layout plan will be proposed to ELVAN company.
Keywords: Facility Location and Design; Mathematical Modelling; Analytical Hierarchy Process